List of the Saber 11 Test, admission exam, academic average, saber protest of students of the psychology program of the University of Magdalena - Iguarán Jiménez, Amanda Miguel (2023)
Introduction: The quality of higher education in Colombia is measured through the indicators that the Saber-Pro Tests show, this exam evaluates generic and specific competencies of the future professional in psychology, therefore, in this research the analysis of the relationship between the academic average, the results obtained in the admission exam, the Saber 11 Tests, the Saber Pro Tests and the academic average of Psychology students at the University of Magdalena. Methods: All students who were admitted between 2012 and 2016 were selected, being 246 female and 86 male, multivariate analysis was used. Objective: to establish the relationship with performance in the SABER PRO standardized test for psychology. Results: The analysis that was carried out was with the 2012 admission cohort by Chi-square of Saber-Pro and the variables of the scores and sociodemographics, finding a statistically significant association between the Saber Pro quartiles and the quartiles of the scores of admission.